Results of an aerial survey of the western population of Anser erythropus (Anserini) in autumn migration in Russia 2017 - Sofia B. Rozenfeld (Nature Conservation Research: Zapovednaâ Nauka, 2019)
The global population of Anser erythropus has rapidly declined since the middle of the 20th century. The decline in numbers has been accompanied by the fragmentation of the breeding range and is considered as «continuing affecting all populations, giving rise to fears that the species may go extinct». Overhunting, poaching and habitat loss are considered to be the main threats. The official estimate of the dimension of the decline is in the range of 30% to 49% between 1998 and 2008. Monitoring and the prospection of new areas are needed for the future conservation of this species. The eastern part of the Nenetsky Autonomous Okrug, the Baydaratskaya Bay and the Lower Ob (Dvuobye) are important territories for the Western main population of Anser erythropus on a flyway scale. Moving along the coast to the east, Anser erythropus can stay for a long time on the Barents Sea Coast, from where they fly over the Baydaratskaya Bay to the Dvuobye. We made aerial surveys and identified key sites and the main threats for Anser erythropus on this part of the flyway. According to our data, the numbers of the Western main population of Anser erythropus amount to 48 580 ± 2820 individuals after the breeding season, i.e. higher than the previous estimates made in autumn in Northern Kazakhstan. The key sites of Anser erythropus in this part of the flyway were identified.